Possible association of urinary incontinence with post-COVID-19: a report of three cases - Francely de Castro Sousa; Liliane Fagundes Estevam; Emília Pio Silva; Nicholas Alfred Joseph Mayers; Marli Carmo Cupertino (Journal of Infection in Developing Countries)
Introduction: The disorder denominated urinary incontinence (UI) has been diagnosed amongst 25–45% of women worldwide. Muscle weakness is one of the more notable symptoms, which is exhibited in the acute form of coronavirus disease 2019 (COVID-19) that compromises the respiratory musculature. Accordingly, this report aims to delineate three cases in women with UI possibly associated with post-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.